GCN5 contributes to intracellular lipid accumulation in human primary cardiac stromal cells from patients affected by Arrhythmogenic cardiomyopathy. Issue 13 (16th June 2022) - Volani, Chiara; Pagliaro, Alessandra; Rainer, Johannes; Paglia, Giuseppe; Porro, Benedetta; Stadiotti, Ilaria; Foco, Luisa; Cogliati, Elisa; Paolin, Adolfo; Lagrasta, Costanza; Frati, Caterina; Corradini, Emilia; et al.
Abstract: Arrhythmogenic cardiomyopathy (ACM) is a genetic disease associated with sudden cardiac death and cardiac fibro‐fatty replacement. Over the last years, several works have demonstrated that different epigenetic enzymes can affect not only gene expression changes in cardiac diseases but also cellular metabolism. Specifically, the histone acetyltransferase GCN5 is known to facilitate adipogenesis and modulate cardiac metabolism in heart failure. Our group previously demonstrated that human primary cardiac stromal cells (CStCs) contribute to adipogenesis in the ACM pathology. Thus, this study aims to evaluate the role of GCN5 in ACM intracellular lipid accumulation. To do so, CStCs were obtained from right ventricle biopsies of ACM patients and from samples of healthy cadaveric donors (CTR). GCN5 expression was increased both in ex vivo and in vitro ACM samples compared to CTR. When GCN5 expression was silenced or pharmacologically inhibited by the administration of MB‐3, we observed a reduction in lipid accumulation and a mitigation of reactive oxygen species (ROS) production in ACM CStCs. In agreement, transcriptome analysis revealed that the presence of MB‐3 modified the expression of pathways related to cellular redox balance. Altogether, our findings suggest that GCN5 inhibition reduces fat accumulation in ACM CStCs, partially by modulating intracellular redox balance pathways.